Effect of a Controlled Ankle Motion Walking Boot on Syndesmotic Instability During Weightbearing: A Cadaveric Study. Issue 8 (19th August 2019) - Lamer, Stéphanie; Hébert-Davies, Jonah; Dubé, Vincent; Leduc, Stéphane; Sandman, Émilie; Ménard, Jérémie; Nault, Marie-Lyne
Background: Syndesmotic injuries can lead to long-term complications; hence, they require careful management. Conservative treatment is adequate when 1 syndesmotic ligament is injured, but surgery is often necessary to achieve articular congruity when 3 syndesmotic ligaments are ruptured. However, there is some controversy over the best treatment for 2-ligament injuries. Purpose: To evaluate the effect of a controlled ankle motion (CAM) walking boot on syndesmotic instability following iatrogenic isolated anterior inferior tibiofibular ligament (AiTFL) injury and combined AiTFL/interosseous ligament (IOL) injuries in a cadaveric simulated weightbearing model. Study Design: Controlled laboratory study. Methods: Ten cadaveric specimens were dissected to expose the tibial plateau and syndesmosis. The specimens were fitted to a custom-made device, and a reproducible axial load of 750 N was applied. Iatrogenic rupture of the syndesmotic ligaments (AiTFL + IOL) was done sequentially. Uninjured syndesmoses, isolated AiTFL rupture, and combined AiTFL/IOL rupture were compared with and without axial loading (AL) and CAM boot. The distal tibiofibular relationship was evaluated using a previously validated computed tomography scan measurement system. Wilcoxon tests for paired samples and nonparametric data were used. Results: The only difference noted in the distal tibiofibular relationship during AL was an increase in the external rotation of the fibula when using the CAM boot. This was observed with AiTFL rupture (8.40° vs 11.17°; P = .009) and combined AiTFL/IOL rupture (8.81° vs 11.97°; P = .005). Conclusion: AL did not cause a significant displacement between the tibia and fibula, even when 2 ligaments were ruptured. However, the CAM boot produced a significant external rotation with 1 or 2 injured ligaments. Clinical Relevance: Further studies are needed to assess the capacity of the CAM walking boot to prevent malreduction when external rotation forces are applied to the ankle. Moreover, special care should be taken during the fitting of the CAM boot to avoid overinflation of the cushions.